“HELP” : TEKNIK DAN IMPLEMENTASI DALAM PROGRAM APLIKASI DAN MULTIMEDIA - Joko Prasetyo, Hendro; Muryanto, (Journal of Computer Science and Technology (JCS-TECH), 2024)
The aim of this research is to show and prove that creating an online help system is not difficult. By creating an application program, we can design and create our own HTML help system and integrate it into the application program that we create. Because when we create an application program, it will usually be accompanied by an application program with help facilities, so that application users will be able to use the application we created according to their expectations. On the other hand, the function of this help system is as a learning tool to turn this help facility into an interactive medium which is expected to be able to help when users use the application program that we created, especially if there are errors when using it. The methodology used in creating this help facility is to use observation methods and reading various literature, both books and by reading media related to creating help media on the internet. Creating a help system will require basic knowledge of creating HTML (Hypertext Markup Language) files. Because this format is the main foundation in creating an HTML Help system, also with a little creativity in terms of layout and design, the display will not be boring and will make users feel at home reading it. The results of this research show that creating an on-line help system is very easy. There is no need to understand programming languages ​​and using help as an interactive medium can actually make it easier for users to understand what their learning objectives are. Because the help system is in multimedia format, where images, sound and animation can be combined into one unit.